Theoretical studies and simulations of mode structure symmetry breaking in tokamak plasmas in the presence of energetic particles. (6th March 2019) - Lu, Z X; Wang, X; Lauber, Ph; Fable, E; Bottino, A; Hornsby, W; Hayward-Schneider, T; Zonca, F; Angioni, C
Abstract: The mode structure symmetry breaking is important for the understanding of the momentum transport induced by micro turbulence and the experimental observation of Alfvénic mode structures driven by energetic particles (EPs) as well as the burning plasma behavior. In this work, the theoretical approach for the analyzes of the global mode structure in the presence of EPs is introduced with various applications. As a brief review of our previous work, the calculation of strongly coupled poloidal harmonics, with a complex 'tilting angle' applied, and the calculation of weakly coupled poloidal harmonics, with EPs' non-perturbative effects taken into account, are introduced. By making use of the theoretical approach, several applications related to the mode structure symmetry breaking are demonstrated. The anisotropic EP impact on the zonal flow residual is calculated. The mode structure symmetry breaking of the EP induced geodesic acoustic mode is studied. The momentum transport related to the mode structure symmetry breaking is estimated. The particle and energy transport is also analyzed and its comparison with the turbulence induced transport is discussed.